IMPLEMENTATION OF LAW NUMBER 7 YEAR 2012 ABOUT HANDLING SOCIAL CONFLICT (Case Study on Prevention of Social Conflict in Probolinggo City) - Prautami Sintaresmi; Slamet Muchsin; Rulam Ahmadi (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
This study aims to find out how the implementation of Law Number 7 of 2012 concerning Handling Social Conflicts in Probolinggo City, knowing the supporting and inhibiting factors of preventing social conflict and strategies to deal the inhibiting factors. The approach used in this study is a qualitative approach. The conclusion of the study shows that the implementation of handling social conflicts in Probolinggo City, especially conflict prevention is carried out by the Integrated Team for Handling Social Conflicts as implementers and the community as policy targets. The supporting factors for preventing social conflict in Probolinggo City are good synergy with human resources for implementing the implementation, geographical conditions and wise use of social media. Meanwhile, the inhibiting factors are that the implementation of social conflict prevention does not involve NGOs/Ormas and universities, the lack of innovation in preventing social conflict, funding support, and the lack of regulatory support. The strategy to overcome obstacles is to collaborate with NGOs/Ormas and universities as partners in preventing social conflict, encouraging innovation in preventing social conflict, increasing coordination with the Regional Government Budget Team and drafting regulations which support the prevention of social conflict.